Czy efektywne miroorganizmy (EMTM) efektywnie podnoszą żyzność gleb? = Are effective microorganisms (EMTM) effective in enhancement of soil fertility? - Jakubus, Monika (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The term Effective Microorganisms (EMTM) refers to a microbial preparation promoting plant growth and health as well as improving soil fertility. In the study the effect of AEMTM preparation (applied at a rate corresponding to 100 L per hectare) in combination with different organic substances (wheat straw, manure, sewage sludge, compost) on soil fertility and liberation of available nutrients was investigated in a 9-month incubation process.
Keywords: efektywne mikroorganizmy; rozkład; substancje organiczne; właściwości glebowe; przyswajalne składniki; effective microorganisms; decomposition; organic substances; soil properties; available nutrients